The response of soil microbial communities to vegetable cropping systems analyzed for RNA- and DNA-based sampling - Gomez Montaño, Lorena (Kansas State University, 2018)
Soil microbial communities play fundamental and complex roles in the productivity of agriculture. However, we still have a limited understanding of the response of microbial communities to different farming systems, such as organic and conventional fertility management regimens. We applied high-throughput sequencing to develop a better understanding of how soil microbial communities (bacteria and fungi) in vegetable production respond to organic or conventional soil fertility management. Specifically, my three studies examined the following questions: 1. How do soil microbial communities from cDNA and DNA samples compare in organic and conventional fertility treatments? 2. How do soil microbial communities in a tomato cropping season respond to long-term organic vs. conventional soil fertility treatments? 3. How do soil bacterial and fungal communities respond to high tunnels, plastic mulch and organic amendments across a tomato cropping season? The first two questions were addressed at the Kansas State University Horticulture and Extension Center in Olathe, KS, using organic and conventional field plots with three levels of fertilizer. We sampled the plots during the development of a tomato crop. The third question was addressed at a commercial farm in Lawrence, KS, during its transition to organic vegetable production, during a tomato crop. The Lawrence experiment included as treatments field plots versus high tunnels, and three organic nutrient amendments. We used 454-pyrosequencing of bacterial and fungal ribosomal markers to compare total resident (DNA) and active microbial communities (cDNA, which is DNA synthesized from a single stranded RNA template) for our first question. We used Illumina MiSeq metabarcoding of bacterial and fungal ribosomal markers for our second and third questions. In all three studies we evaluated bacterial and fungal community responses using Simpson´s diversity index, Simpson´s evenness and richness for each experiment. For the first question, when we compared DNA and cDNA, bacterial diversity was higher in cDNA samples from organic compared to conventional management. In addition, fungal diversity from cDNA samples was higher than from DNA samples. In contrast, in the second question, bacterial and fungal diversity indices did not differ in the tomato crop under organic and conventional management systems. For our third question, high tunnels did not affect bacterial or fungal diversity. Use of plastic mulch for a tomato crop in open field plots did not affect bacterial richness, but decreased fungal richness compared to open field plots without plastic mulch. High-throughput sequencing provides a new perspective on the structure and dynamics of these communities. Information from this approach will ultimately improve our ability to manage soil for sustainable productivity by promoting beneficial microorganisms and suppressing pathogenic ones.
Keywords: Microbial communities; Vegetable cropping systems; High-throughput sequencing; Sustainable agriculture